A qualitative inquiry into subject ellipsis in Acehnese coordinative constructions - Muhammad Iqbal; Mulyadi Mulyadi; Ida Basaria; Dardanila Dardanila (Studies in English Language and Education, 2024)
The ellipsis of the subject is used to make sentences more concise and effective. Subject ellipsis can occur in written and spoken languages. This research examines the ellipsis of subjects in the coordinative constructions of the Acehnese language. A qualitative approach was employed for this research, with data collected from three different locations in Pidie Regency, Aceh, Indonesia: Padang Tiji Sub-district (located in the westernmost area), Mutiara Timur Sub-district (located in the central area) and Tangse Sub-district (located in the easternmost area). The research data consists of both oral and written data obtained from informants. Data collection was conducted using the listening-engagement technique and free-engaged listening techniques. Data analysis was conducted using the distribution method with basic and advanced techniques. The research results revealed that the subject ellipsis occurred in the second clause. The ellipsis occurred if there was the same syntactic function as the ellipsis condition. If the subject was not identical, the ellipsis could not be made even if the syntactic function was similar. The ellipsis of the subject in the coordinative construction of the Acehnese language occurs in the coordinative construction of the Acehnese language expressing: 1) addition relationship, which is marked by the conjunction ngn/dan (and), lom (and/again/then), and sireuta (also), 2) contradictory relationship is expressed with the conjunctions malngkan (but), 3) oppositional relations is expressed with the conjunctions tapi (nonetheless), 4) optional relationship is marked by the conjunction of the atawa (or), and 5) supplementary relationships is marked by the conjunction of the teuma (then).